Consumers' attitudes towards alternatives to conventional meat products: Expectations about taste and satisfaction, and the role of disgust. (1st February 2023) - Vural, Yeliz; Ferriday, Danielle; Rogers, Peter J.
Abstract: The livestock sector has environmental, health, and animal welfare impacts. This UK-based, quantitative study aimed to elucidate consumers' valuation of alternatives to conventional meat products. In an online study, 151 meat eaters and 44 non-meat eaters were shown pictures of meat, dairy, and bakery products, including beef burger, cheese sandwich and blueberry muffin. Each product was evaluated with three different labels (e.g., 'conventional', 'plant-based' and 'cultured' for beef burger). Participants rated expected taste pleasantness, fullness, satisfaction, healthiness, disgust and willingness-to-pay for each product/label combination. The results obtained demonstrate that alternatives to conventional meat products overall are acceptable to both meat and non-meat eaters. Although meat eaters' expected plant-based meat alternatives to be less satisfying, due to lower expected taste pleasantness and fillingness (Cohen's d = 0.14 to 0.63), they perceived the plant-based alternatives to be more healthy ( d ≥ 1.18). Cultured meat products were perceived by meat eaters to be equally or more healthy, but more disgusting ( d ≥ 0.41), than conventional meat products. These results suggest there is an opportunity to promote (motivate) acceptance of alternatives to conventional meat products based on their perceived healthiness, to at least partly balance reduced expected taste pleasantness and other negative attributes (i.e., barriers).